2001
DOI: 10.1097/00009957-200101000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features of Supracondylar Fractures of the Humerus in Chinese Children

Abstract: We studied 450 children with a supracondylar fracture of the humerus in the period 1991 to 1995, and were able to collect full management details in 403 of them (253 boys and 150 girls). The median age at presentation was 6 years (6.6 years in boys, and 5 years in girls), with the nondominant humerus 1.5 times more commonly injured. Fifteen percent of children presented more than 1 day after the injury. Garland type III fractures constituted 45% of cases, type I 30%, and type II 24%, with flexion type fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
83
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 18 publications
10
83
0
6
Order By: Relevance
“…Fall injury causes major injury. In our study it has been found that fall while playing and fall from bicycle causes maximum injury in the early group which is 33.33% while in the late group it was found that fall while playing causes maximum injury which is 42.1%, which is consistent with other studies [35][36][37][38][39] . In our study it was found that radial nerve was the commonest nerve involved, although slightly higher than described in the literature in early group (14.8%) and median nerve palsy (7.4%), while patients presenting late had no such complications [43][44] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Fall injury causes major injury. In our study it has been found that fall while playing and fall from bicycle causes maximum injury in the early group which is 33.33% while in the late group it was found that fall while playing causes maximum injury which is 42.1%, which is consistent with other studies [35][36][37][38][39] . In our study it was found that radial nerve was the commonest nerve involved, although slightly higher than described in the literature in early group (14.8%) and median nerve palsy (7.4%), while patients presenting late had no such complications [43][44] .…”
Section: Discussionsupporting
confidence: 92%
“…In our study age of the patients was 8.23± 2.981 years in early group and 7.84 ± 3.95 years in the late group which is nearly similar to the studies done by others [35][36] . Males were found to be more commonly involved both in early and late groups which are 63.0 % and 68.4 % respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Dentre estas, as fraturas supracondilianas do úmero são responsáveis por até 50 a 70% dos casos (2)(3)(4) , acometendo principalmente crianças na faixa etária entre cinco e sete anos de idade (5) . As lesões ocorrem predominantemente à esquerda, ou do lado não dominante (5)(6)(7) .…”
Section: Introductionunclassified